Potential Studies of Permeable Concrete With Palm Oil Fuel Ash (POFA) in Treating Laundry Greywater - Mohd Sidin, Sarah; Radin Mohamed, Radin Maya Saphira (Recent Trends in Civil Engineering and Built Environment, 2021)
Laundry greywater contain various pollutant with high concentration such as organic carbon, bacteria, and solids. To protect the fresh water quality, it is forbidden to directly discharge laundry greywater runoff to the stream. Therefore, the study is aimed to treat the laundry greywater by using permeable concrete with palm oil fuel ash (POFA). The focus of this study is to discuss and summarize the major finding of these collective studies related to: (a) Laundry greywater characteristics (b) The efficiency of the palm oil fuel ash (POFA) as adsorbent materials in wastewater related study based on previous studies analysis. Review analysis indicated that UPOFA has larger specific surface area (1.962 m2/g) and has substitute cement by 20, 40, 60 and 80% of weight. The optimum dosage of POFA is 8 g/L to remove pollutant in sewage wastewater and the 4 g/L for domestic wastewater. The findings advocate that the certain amount of POFA successfully reduce a large amount of pollutant in the wastewater due to presence of high concentration of alumina, calcium, potassium and silica that can be used for synthesising active compounds .